Self-Regulated Learning in Music Education: A Structural Model of Social Support and Performance-Related Challenges - Zarza-Alzugaray, Francisco Javier; Grau Ramón, Sara; Casanova, Osca; Zarza-Alzugaray, María Begoña (Universitas Negeri Semarang, 2025)
This study analyses the relationship between self-regulated learning (SRL), music performance anxiety (MPA), and social support in a sample of 72 students at music conservatories in Spain. Using a structural equation model, the direct and indirect effects of psychological and social factors on self-regulation are examined, with instrument practice hours as a mediating variable. The results show that self-regulation is boosted by social support from teachers and by hours of study, while performance anxiety and helplessness have significant adverse effects. In addition, performance anxiety is associated with higher levels of helplessness and with an unfavourable early educational context. Support from family and friends is negatively associated with helplessness, indicating a protective role, although its direct influence on instrument practice is limited. The final model explains 52% of the variance in self-regulated learning, suggesting that support quality and perceived independence are decisive and highlighting the importance of pedagogical practices that foster self-regulation, metacognition, and emotional resilience in music education.